Adhesive composition, manufacturing method thereof, and optical device

The adhesive composition for optical devices, featuring a blend of epoxy, oxetane, silane, and silica with specific particle size distributions, addresses the challenges of stability and performance under temperature and impact, achieving low expansion and elastic modulus for improved adhesion and durability.

JP7667845B1Active Publication Date: 2025-04-23TOKUYAMA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023214071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2025-04-23
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

Adhesives used in optical devices face challenges such as easy displacement due to external factors, high linear expansion coefficients, and high storage elastic moduli, which affect their stability and performance under temperature changes and impact.

Method used

The adhesive composition includes a combination of an epoxy compound, an oxetane compound, a silane coupling agent, a photoacid generator, and silica, with specific particle size distributions and content ratios of large and small particle size silica to achieve low linear expansion coefficients and storage elastic moduli.

Benefits of technology

The adhesive composition exhibits excellent operability, low linear expansion coefficient, and low storage elastic modulus, effectively preventing positional deviation of optical device components due to temperature changes and impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667845000001_ABST
    Figure 0007667845000001_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive composition which has good operability during use and a low linear expansion coefficient and storage modulus after curing, a method for producing the same, and an optical device whose components are less likely to shift due to temperature changes and impacts. [Solution] The adhesive composition of the present invention contains (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica, the (E) silica having (E-1) large particle size silica and (E-2) small particle size silica, the average particle size D50 of the (E-1) large particle size silica is 0.5 μm or more and 1.5 μm or less, the average particle size D50 of the (E-2) small particle size silica is less than 0.5 μm, the difference between the average particle size D50 of the (E-1) large particle size silica and the average particle size D50 of the (E-2) small particle size silica is 0.5 μm or more, and the content of the (E-2) small particle size silica in the (E) silica is 10 mass% or more and 50 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition, a method for producing the same, and an optical device. [Background technology]

[0002] In the manufacture of optical devices such as smartphone camera modules and in-vehicle optical sensors, a method of bonding optical components such as lenses and image sensors to a substrate or housing using a photocationically curable adhesive, which is an ultraviolet-curable adhesive, is commonly used. As such a photocationically curable adhesive, for example, from the viewpoint of exhibiting excellent adhesive strength and mounting accuracy, an adhesive composition containing an epoxy compound, an oxetane compound, a photocationic polymerization initiator, a silane coupling agent, and silica has been proposed (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-69039 A Summary of the Invention [Problem to be solved by the invention]

[0004] Adhesives used in optical devices are required to have properties that prevent optical components from shifting or falling off due to external factors during use. Specifically, the adhesive after curing is required to have a low linear expansion coefficient, that is, to not expand or contract easily due to temperature changes, and flexibility to absorb shock, that is, to have a low storage modulus. In addition, when using the adhesive, it is required to have the operability to smoothly suck or discharge the adhesive with an applicator such as a dropper or dispenser and place it on the bonding site.

[0005] An object of the present invention is to provide an adhesive composition that has good operability during use and has a low linear expansion coefficient and storage modulus after curing, a method for producing the same, and an optical device whose components are less likely to become displaced due to temperature changes and impacts. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention includes the following inventions.

[0007] The present invention [1] comprises an adhesive composition comprising (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica, the (E) silica having (E-1) large particle size silica and (E-2) small particle size silica, the average particle size D50 of the (E-1) large particle size silica being 0.5 μm or more and 1.5 μm or less, the average particle size D50 of the (E-2) small particle size silica being less than 0.5 μm, the difference between the average particle size D50 of the (E-1) large particle size silica and the average particle size D50 of the (E-2) small particle size silica being 0.5 μm or more, and the content of the (E-2) small particle size silica in the (E) silica being 10 mass% or more and 50 mass% or less.

[0008] The present invention [2] includes the adhesive composition according to [1], in which the content of (E) silica per 100 parts by mass of the total of (A) the epoxy compound and (B) the oxetane compound is 100 parts by mass or more and 200 parts by mass or less.

[0009] The present invention [3] includes an optical device comprising a cured product of the adhesive composition according to [1] or [2].

[0010] The present invention [4] includes a method for producing an adhesive composition containing (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica, comprising mixing (E-1) large-particle silica having an average particle size D50 of 0.5 μm or more and 1.5 μm or less and (E-2) small-particle silica having an average particle size D50 of less than 0.5 μm and having a difference of 0.5 μm or more from the average particle size D50 of the large-particle silica (E-1) such that the content of (E-2) small-particle silica in (E) silica is 10% by mass or more and 50% by mass or less. Effect of the Invention

[0011] The adhesive composition of the present invention has good operability during use and has a good linear expansion coefficient and storage modulus after curing. In addition, the optical device of the present invention can suppress displacement of parts due to temperature changes and impacts. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 shows a schematic cross-sectional view of a camera module of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] An example of an embodiment of the present invention will be described in detail below. However, the present invention is not limited to the embodiment described below, and can be modified as desired without departing from the gist of the present invention.

[0014] An example of the adhesive composition of the present invention (hereinafter also referred to as "the composition") is a photocationically curable adhesive, which contains (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica. Each component will be described in detail below.

[0015] (A) Epoxy compound The epoxy compound has one or more epoxy groups in the molecule, and preferably has two or more epoxy groups in the molecule. The composition contains an epoxy compound, and can be cured by a polymerization reaction to bond parts together. In addition, the epoxy compound has multiple epoxy groups, which further improves the strength of the cured product of the composition.

[0016] The epoxy compound is preferably an alicyclic epoxy compound having an alicyclic structure and an epoxy group, more preferably an alicyclic epoxy compound having an epoxy group (alicyclic epoxy group) composed of two adjacent carbon atoms and an oxygen atom that constitute an alicyclic ring. Since such an epoxy compound has rigidity, the volume expansion due to heat is suppressed in the cured product of the present composition, and the linear expansion coefficient can be further reduced.

[0017] The alicyclic epoxy compound preferably has two or more epoxy groups in the molecule. In this case, the two or more epoxy groups may all be alicyclic epoxy groups, or may be a combination of alicyclic epoxy groups and non-alicyclic epoxy groups. Preferably, all the epoxy groups are alicyclic epoxy groups.

[0018] Examples of such alicyclic epoxy compounds include compounds represented by the following formulas (A1) to (A3). These alicyclic epoxy compounds may be used alone or in combination of two or more. In the present composition, preferably, at least the compound of formula (A1) is used. More preferably, the alicyclic epoxy compound of formula (A1) is used in combination with the alicyclic epoxy compound of formula (A2) and / or (A3).

[0019] [ka]

[0020] In the above formula, R 1represents an alkylene group having 4 to 8 carbon atoms, and n represents, for example, an integer of 1 to 5. X represents a single bond, an ether bond (-O-), a thioether bond (-S-), or an alkylene group having 1 to 3 carbon atoms. R 2 represents an alkylene group having 1 to 3 carbon atoms, etc.

[0021] Specific examples of the alicyclic epoxy compound include CELLOXIDE 8000, CELLOXIDE 2021P, CELLOXIDE 2081, CELLOXIDE 2083, CELLOXIDE 2085, EPOLEAD GT401, and EHPE3150 manufactured by Daicel Corporation; and TTA21, TTA22, TTA26, and TTA3150 manufactured by Sun Chemical Co. These may be used alone or in combination of two or more kinds.

[0022] When the alicyclic epoxy compound of formula (A1) is used in combination with other alicyclic epoxy compounds (for example, the alicyclic epoxy compounds of formula (A2) and / or formula (A3)), the mixing ratio of these (other alicyclic epoxy compounds:alicyclic epoxy compound of formula (A1)) is, for example, 1:1 to 6:1, preferably 2:1 to 3:1, by mass ratio. This can further improve the linear expansion coefficient and storage modulus of the cured product of the present composition.

[0023] The present composition may further contain a bisphenol type epoxy resin as an epoxy compound in addition to the above alicyclic epoxy compound, which allows the crosslink density of the cured product of the present composition to be adjusted and allows the linear expansion coefficient and storage modulus to be improved.

[0024] Examples of bisphenol type epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AD ​​type epoxy resins.

[0025] The weight average molecular weight of the bisphenol type epoxy resin is, from the viewpoint of the linear expansion coefficient of the cured body, for example, 1200 or less, preferably 800 or less, more preferably 600 or less, and for example, 300 or more.

[0026] Specific examples of bisphenol type epoxy resins include jER806, jER806H, jER807, jER825, jER827, jER828, jER828EL, jER828US, jER828XA, and jER834 manufactured by Mitsubishi Chemical Corporation; YD-8125 and YDF-8170C manufactured by Nippon Steel Chemical & Material Co., Ltd.; and Epicron 830, Epicron 830-S, Epicron 835, Epicron 840, Epicron 840-S, Epicron 850, Epicron 850-S, and Epicron 850-LC manufactured by DIC Corporation. These may be used alone or in combination of two or more kinds.

[0027] When an alicyclic epoxy compound and a bisphenol type epoxy resin are used in combination, the mass ratio of the alicyclic epoxy compound to the bisphenol type epoxy resin is, for example, 1:1 to 6:1, and preferably 3:1 to 4:1. This allows the linear expansion coefficient, storage modulus, glass transition point, and the like to be adjusted to desired values ​​as an adhesive used in optical devices such as camera modules or optical sensors. The content of all epoxy compounds in the composition is, for example, 10 mass% or more, preferably 25 mass% or more, and, for example, 60 mass% or less, preferably 45 mass% or less. This further improves the adhesive strength and mounting accuracy.

[0028] (B) Oxetane Compound An oxetane compound has one or more oxetane groups in a molecule. Since an oxetane compound has a faster propagation reaction rate than an epoxy compound, the inclusion of an oxetane compound in the composition makes it possible to efficiently advance the polymerization reaction during curing, thereby reducing the brittleness peculiar to epoxy resins and improving flexibility and toughness.

[0029] Examples of the oxetane compound include 3-ethyl-3-hydroxymethyloxetane, xylylene bisoxetane, oxetanyl silsesquioxetane, 3-ethyl-3-phenoxymethyloxetane, 2-ethylhexyloxetane, 3-ethyl-3-(cyclohexyloxy)methyloxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, phenol novolac oxetane, etc. These may be used alone or in combination of two or more.

[0030] The content of the oxetane compound is, in terms of the mass ratio of the epoxy compound to the oxetane compound, for example, 4:1 to 20:1, or preferably 8:1 to 10:1, thereby making it possible to achieve a good balance between the curing speed and the physical properties of the cured product.

[0031] (C) Silane coupling agent The silane coupling agent is a silicon compound having both an organic reactive site and an inorganic reactive site. The present composition can improve the adhesive strength by including the silane coupling agent.

[0032] Examples of silane coupling agents include vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. These may be used alone or in combination of two or more. From the viewpoint of the affinity between the epoxy compound and the oxetane compound, 3-glycidoxypropyltrimethoxysilane is preferably used.

[0033] The content of the silane coupling agent is, for example, 0.5 parts by mass or more, preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and, for example, 10 parts by mass or less, preferably 5 parts by mass or less, more preferably 4.5 parts by mass or less, based on 100 parts by mass of the total amount of the epoxy compound and the oxetane compound. By setting the content in this range, the adhesiveness of the present composition can be further improved.

[0034] (D) Photoacid generator The photoacid generator generates an acid when irradiated with energy rays or radiation, and is blended in the present composition as, for example, a polymerization initiator.

[0035] Examples of photoacid generators include onium salts that release Lewis acids when irradiated with energy rays or the like. Examples of such onium salts include sulfonium salts and iodonium salts, and preferably sulfonium salts. Examples of sulfonium salts include the compound represented by the following formula (D1) (diphenyl[4-(phenylthio)phenyl]sulfonium salt) and the compound represented by (D2). Examples of iodonium salts include the compound represented by the following formula (D3) or (D4). These may be used alone or in combination of two or more.

[0036] [ka]

[0037] In the above formula, X - are SbF6, respectively. - , PF6 - , PF3(C2F5)3 - , B(C6F5)4 - , BF4 - , AsF6 - These anions are:

[0038] The content of the photoacid generator is, for example, 0.5 parts by mass or more, preferably 1 part by mass or more, and for example, 10 parts by mass or less, preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of the epoxy compound and the oxetane compound. By setting the content in this range, the present composition can be cured by ultraviolet irradiation for a shorter period of time.

[0039] (E) Silica The silica includes (E-1) large particle size silica and (E-2) small particle size silica. Preferably, the silica consists of only large particle size silica and small particle size silica.

[0040] (E-1) Large particle size silica The large-particle silica has an average particle diameter D50 of 0.5 μm or more and 1.5 μm or less, preferably 0.7 μm or more and 1.5 μm or less, more preferably 1.2 μm or more and 1.5 μm or less. The large-particle silica preferably has a D10 / D90 value of 0.7 or less. D10 / D90 is an index showing the uniformity of particle size distribution, and the smaller this value, the higher the uniformity of the particle size distribution, meaning that the number of silica particles of 0.5 μm or more and 1.5 μm or less is large. This makes it easy to reduce the storage modulus due to the interaction between the large-particle silica and the small-particle silica. In the present invention, D10, D50 and D90 are the particle sizes at which the volume accumulation in the particle size distribution curve obtained by the laser diffraction method is 10%, 50% and 90%. Specifically, 100 mg of silica is mixed with 40 ml of water and dispersed for 10 minutes with an ultrasonic homogenizer at an output of 40 W. The sample is then measured using a laser diffraction particle size distribution measuring device to obtain a particle size distribution curve, from which D10, D50 and D90 can be calculated.

[0041] The specific surface area of ​​large particle silica is, for example, 0.5 m 2 / g or more, preferably 1m 2 / g or more, more preferably 1.5m 2 / g or more, and for example, 5m 2 / g or less, preferably 4.5m 2 / g or less, more preferably 4m 2 / g or less. By setting the specific surface area of ​​the large particle size silica to the above range, even if the composition contains a high content of silica, the increase in viscosity can be suppressed and high fluidity can be ensured. The specific surface area of ​​silica is the BET specific surface area measured by the BET method.

[0042] The content of large particle silica in silica is, for example, 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more, and for example, 90 mass% or less, preferably 85 mass% or less, preferably 80 mass% or less.Furthermore, for example, 80 mass% or more, preferably 90 mass% or more, more preferably 110 mass% or more, and for example, 200 mass% or less, preferably 180 mass% or less, more preferably 150 mass% or less, relative to 100 mass% of the total amount of epoxy compound and oxetane compound.

[0043] (E-2) Small particle size silica The small particle size silica has an average particle size D50 of less than 0.5 μm, and for example, 0.1 μm or more, preferably 0.3 μm or more. In the small particle size silica, D10 / D90 is preferably 0.7 or less.

[0044] The specific surface area of ​​small particle silica is, for example, 5 m 2 / g or more, preferably 6.5m 2 / g or more, more preferably 8m 2 / g or more, and for example, 20m 2 / g or less, preferably 18m 2 / g or less, more preferably 16m 2 / g or less. By making the specific surface area of ​​the small particle silica equal to or more than the lower limit, the sedimentation of the silica during storage of the composition can be suppressed, and the composition has excellent sedimentation resistance. In addition, by making the specific surface area of ​​the small particle silica equal to or less than the upper limit, the fluidity of the composition can be further improved.

[0045] The content (content ratio) of small particle silica in silica is 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less. In addition, for example, 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and for example, 80 parts by mass or less, preferably 60 parts by mass or less, more preferably 40 parts by mass or less, relative to 100 parts by mass of the total amount of the epoxy compound and the oxetane compound. By setting the content of small particle silica within the above range, it is possible to reduce (improve) the storage modulus of the cured product of the composition while maintaining the fluidity of the composition. Therefore, in an optical device bonded with a cured product of the composition, it is possible to reduce the effect of impact and suppress the displacement or falling off of parts.

[0046] The difference (particle size difference) between the average particle size D50 of the large-particle silica and the average particle size D50 of the small-particle silica is 0.5 μm or more, preferably 0.8 μm or more, more preferably 1.1 μm or more, and for example, 5.0 μm or less, preferably 3.0 μm or less, more preferably 2.0 μm or less. If the particle size difference is below the lower limit, the voids between the silica particles in the cured product of the composition become large, and the silica region and the resin region are easily separated into a layered state. As a result, the hard silica region is unevenly distributed, stress concentration is easily generated in the silica region, and the storage modulus may become high.

[0047] Preferably, both the large-particle silica and the small-particle silica are spherical silica. Specifically, the shapes of 1,000 silica particles contained in the silica are observed with a scanning electron microscope, and the sphericity of each particle is measured. If the average is 0.9 or more, the silica is considered to be spherical silica. The sphericity is calculated by the formula: 4π×(area) / (perimeter) 2The measurement can be performed using an image processing program (e.g., AnalySIS manufactured by Soft Imaging System GmbH). This makes it possible to suppress an increase in viscosity and ensure high fluidity even if the composition contains a high content of silica.

[0048] Moreover, both the large particle size silica and the small particle size silica are preferably independent. Being independent means that the silica is unlikely to form aggregates (either primary aggregates or secondary aggregates). Specifically, for silica, (specific surface area) / (calculated value of specific surface area) is in the range of 0.85 to 1.35. The specific surface area is measured by the BET method. The calculated value of the specific surface area is calculated by 6 / (density×D50), and the density of silica in this calculation is 2.2 g / cm. 3 This makes it easier for the silica to exist independently in the composition without agglomeration, and stress concentration is less likely to occur, making it easier to reduce the storage modulus of the cured body of the photocationically curable adhesive.

[0049] The total content of silica (i.e., the sum of large-particle silica and small-particle silica) is, for example, 90 parts by mass or more, preferably 100 parts by mass or more, more preferably 130 parts by mass or more, and for example, 300 parts by mass or less, preferably 200 parts by mass or less, more preferably 170 parts by mass or less, relative to 100 parts by mass of the total amount of the epoxy compound and the oxetane compound. By setting the amount of silica in the above range, it is possible to suppress the increase in viscosity and increase the fluidity while maintaining a low linear expansion coefficient. Therefore, it is possible to improve the workability when the composition is sucked or discharged for use, and to exhibit suitable physical properties as an adhesive for use in optical devices such as camera modules and optical sensors.

[0050] The silica of the present composition may be commercially available silica for each of the large particle size silica and the small particle size silica, or may be produced by a known method such as a dry method or a wet method. In addition, commercially available or produced silica may be used by adjusting the specific surface area to a desired range by sieving, air classification, etc. The dry method is a method in which silica powder is generated by burning a silicon compound and grown in and near the flame. Specific examples of the dry method include the method described in WO2020 / 175160. In the dry method, the average particle size and specific surface area can be adjusted by adjusting the combustion and cooling conditions of the flame and the amount of heat removed. Examples of the wet method include the sol-gel method. The sol-gel method is a method in which a silicon alkoxide is hydrolyzed and polycondensed in a reaction medium containing a catalyst to generate a silica sol, which is then gelled and dried. A specific example of the sol-gel method is the method described in WO2018 / 096876. In the sol-gel method, the average particle size and the specific surface area can be adjusted by adjusting the reaction temperature, the concentration of the reaction solution, and the dropping speed of the reaction solution. The silica may be surface-treated with a silane coupling agent or the like.

[0051] The composition has good fluidity, and furthermore, when cured, has a low linear expansion coefficient and a low storage modulus. The reason for this is unclear, but the present inventors believe it to be as follows. Note that the present invention is not limited to the following.

[0052] By blending a high content of silica in the adhesive, the proportion of resin components (polymers of epoxy compounds and oxetane compounds) with a relatively large linear expansion coefficient can be reduced, and the linear expansion coefficient of the cured adhesive can be reduced (improved). However, on the other hand, the proportion of relatively hard silica increases, so the storage modulus of the cured adhesive increases and the flexibility of the cured adhesive decreases. In addition, the high content of silica reduces the fluidity of the adhesive, so that when used, the suction and discharge from the discharge device are not smooth, and the operability decreases. Thus, it was thought that it was difficult to achieve both a low storage modulus and good fluidity while reducing the linear expansion coefficient with the conventional single silica blend.

[0053] In response to this, the present inventors have solved the above problem by including in the adhesive composition of the present invention two specific types of silica, that is, specific large-sized silica and specific small-sized silica having a specific particle size difference relationship, in specific amounts. Specifically, by replacing a part of the large-sized silica having a low linear expansion coefficient with small-sized silica having a low linear expansion coefficient, the concentrated stress on the large-sized silica is dispersed to the surrounding resin. In addition, by making the particle size difference between the large-sized silica and the small-sized silica to be a specific value or more, the small-sized silica is appropriately arranged in the gaps between the large-sized silica, and layer separation (separation between silica and resin) is suppressed, thereby reducing the concentrated stress on the silica region. By reducing these concentrated stresses, the storage modulus is reduced. In addition, by adjusting the amount of the small-sized silica to an appropriate amount, the decrease in fluidity is suppressed, and both the linear expansion coefficient and the storage modulus are reduced while maintaining good fluidity.

[0054] (Other ingredients) The present composition may contain other components other than (A) to (E) within a range that does not impair the effects of the present invention. Examples of other components include fillers other than silica, thermal cationic polymerization initiators, curing accelerators, flame retardants, rubber particles, thickeners, defoamers, leveling agents, antioxidants, colorants, photosensitizers, etc. In addition, in the present composition, the filler is preferably composed only of silica from the viewpoint of achieving both the linear thermal tension coefficient and the storage modulus.

[0055] (Method of manufacturing adhesive composition) As an example of a method for producing the present composition, (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, (E-1) large particle size silica, and (E-2) small particle size silica are mixed so that the content of small particle size silica in the silica is 10 mass % or more and 50 mass % or less.

[0056] For example, (A) the epoxy compound, (B) the oxetane compound, (C) the silane coupling agent, (D) the photoacid generator, (E-1) the large particle size silica, and (E-2) the small particle size silica may be mixed simultaneously, or these components may be mixed in any suitable order.

[0057] Also, (E-1) large-particle silica and (E-2) small-particle silica may be mixed separately to prepare mixed silica (i.e., (E) silica), and this (E) silica may be mixed with (A) epoxy compound, (B) oxetane compound, (C) silane coupling agent, and (D) photoacid generator. In this case, the mixing order of (A), (B), (C), (D), and (E) is not limited, and for example, they may all be mixed at the same time, or may be mixed in an appropriate order.

[0058] The mixing method is not limited, and the mixture can be produced by a known method using a known mixing device such as a blender, a mixer, etc. If necessary, the mixing may be carried out in a heated atmosphere or an inert gas atmosphere.

[0059] (Physical properties of the cured product of the adhesive composition of the present invention) The cured product of the composition is obtained by carrying out the curing method described later on the composition. The linear expansion coefficient of the cured product of the composition is preferably 60 ppm / K or less, more preferably 50 ppm / K or less, and even more preferably 45 ppm / K or less. If the linear expansion coefficient of the cured product is equal to or less than the upper limit, the thermal expansion and thermal contraction are small, and the cured product has excellent low expansion properties. Therefore, when a part of an optical device (for example, a lens, an image sensor, etc.) is fixed using the composition, even if the optical device is heated or cooled, the volume change at the bonding point is mitigated, so that the displacement and falling off (dislodging) of the part caused by temperature change can be suppressed. Therefore, according to the composition, an optical device that is less susceptible to thermal effects can be provided. The lower limit is not limited, but is, for example, 30 ppm / K or more, preferably 35 ppm / K or more. The linear expansion coefficient can be measured, for example, by a compression load method using a thermomechanical analyzer.

[0060] The storage modulus E' of the cured product of the composition is preferably 8 GPa or less, more preferably 7.5 GPa or less, and even more preferably 7 GPa or less. If the storage modulus of the cured product is equal to or less than the upper limit, the flexibility is excellent. Therefore, when the composition is used to fix a part, even if the optical device is subjected to an impact, the adhesive portion absorbs the impact, so that it is possible to suppress the part from being displaced or falling off due to the impact. Therefore, the composition can provide an optical device that is less susceptible to mechanical influences. The lower limit is not limited, but is, for example, 4 GPa or more, preferably 5 GPa or more. The storage modulus E' is, for example, a value at 25°C when a 1 mm thick cured product is measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz.

[0061] The glass transition temperature Tg of the cured product of the present composition is preferably 130° C. or higher, more preferably 140° C. or higher, and even more preferably 150° C. or higher. If the glass transition temperature of the cured product is equal to or higher than the lower limit, the heat resistance of the bonded portion is excellent. The upper limit is not limited, but is, for example, 250° C. or lower, preferably 200° C. or lower.

[0062] (Application) The present composition is not limited to adhesive applications, and can be used to bond various parts. The present composition can be bonded (cured) by UV irradiation, and the cured product has a good linear expansion coefficient and storage modulus, so that it can be suitably used for manufacturing optical devices. An optical device is a device equipped with optical components such as lenses and mirrors, and examples thereof include a camera module and an optical sensor equipped with the module. Such optical components such as a camera module and an optical sensor are designed according to various purposes of use, such as for smartphones and in-vehicle use. Hereinafter, an example of the use of the present composition for bonding a camera module will be described as an application.

[0063] (Camera module) An example of a camera module including a cured product of the adhesive of the present invention will be described with reference to FIG.

[0064] The camera module 1 of the present invention includes a lens 2, a lens barrel 3, a seal glass 4, an imaging element 5, a circuit board 6, a housing 7, and a cured body 8.

[0065] The lens 2 is fixed to the lens barrel 3 inside the lens barrel 3 via the hardened body 8. That is, the hardened body 8 is disposed between the outer circumferential surface of the lens 2 and the inner circumferential surface of the lens barrel 3.

[0066] The lens barrel 3 is fixed to the housing 7 inside the housing 7 via the hardened body 8. That is, the hardened body 8 is disposed between the outer circumferential surface of the housing 3 and the inner circumferential surface of the housing 7.

[0067] The seal glass 4 is fixed to the housing 7 through the hardened body 8 on the inside of the housing 7. That is, the hardened body 8 is disposed between the outer peripheral surface of the seal glass 4 and the inner peripheral surface of the housing 7. The seal glass 4 may also serve as an infrared cut filter having a function of blocking infrared rays.

[0068] The circuit board 6 has its upper surface (the surface on the lens 2 side) fixed to the housing 7 via the hardened body 8. That is, the hardened body 8 is disposed between the upper surface of the circuit board 6 and the lower surface of the housing 7. In addition, the imaging element 5 is mounted on the circuit board 6.

[0069] The camera module 1 of the present invention is produced by applying or flowing the present composition to (1) the bonding area between the lens 2 and the barrel 3, (2) the bonding area between the sealing glass 4 and the housing 7, (3) the bonding area between the barrel 3 and the housing 7, and (4) the bonding area between the circuit board 6 and the housing 7, and then curing the composition.

[0070] The composition can be cured, for example, by ultraviolet irradiation. The illuminance and time of ultraviolet irradiation are not limited as long as the resin component of the composition reacts. For example, 2 More than 1000mW / cm 2 The time may be 10 seconds or more and 10 minutes or less. The number of irradiations may be one or more. In the case of multiple irradiations, for example, first, low-intensity ultraviolet light may be irradiated to perform temporary fixing, and then high-intensity ultraviolet light may be irradiated to perform permanent fixing. In addition, a heating step may be performed after the ultraviolet light irradiation. This can promote post-curing and release the thermal distortion caused by ultraviolet light irradiation to increase the adhesive strength. The heating conditions may be, for example, a temperature of 50°C or more and 150°C or less for 0.5 hours or more and 5 hours or less. As a method for applying and flowing the present composition, for example, a known application tool such as a dropper or a dispenser may be used.

[0071] The camera module 1 thus obtained is bonded at the bonding locations (1) to (4) above with a cured product of the present composition. Therefore, the bonding locations are less susceptible to thermal expansion and have an appropriate degree of flexibility. This makes it possible to prevent the lens 2, lens barrel 3, sealing glass 4, circuit board 6, and housing 7 from shifting or falling off due to temperature changes and impacts. As a result, for example, it is possible to prevent optical axis shift and focus shift with respect to the imaging element 5, and color change due to shifting of the infrared cut filter (sealing glass 4).

[0072] 1, the cured body 8 is disposed at each of the adhesion locations (1) to (4), but for example, although not shown, the cured body 8 may be disposed at any one of the adhesion locations (1) to (4). In particular, from the viewpoint of being directly affected by the lens 2, it is preferable that the cured body 8 is disposed at least at the adhesion location (1). EXAMPLES

[0073] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples and comparative examples. Various materials used and physical property measurement conditions are described below.

[0074] (A) Epoxy compound A-1: "Celloxide 2081" (the following alicyclic epoxy compound, manufactured by Daicel Corporation) A-2: "Celloxide 2021P" (the following alicyclic epoxy compound, manufactured by Daicel Corporation) A-3: "jER828" (bisphenol A type epoxy resin, weight average molecular weight 370, manufactured by Mitsubishi Chemical Corporation)

[0075] [ka]

[0076] (B) Oxetane Compound B-1: 3-Ethyl-3-hydroxymethyloxetane (OXT-101, manufactured by Toagosei Co., Ltd.) (C) Silane coupling agent · C-1: 3-Glycidoxypropyltrimethoxysilane (“KBM-403”, manufactured by Shin-Etsu Silicone Co., Ltd.) (D) Photoacid generator · D-1: Diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate (“CPI-101A”, manufactured by San-Apro Ltd.)

[0077] (E) Silica · E-a: Sansil SS-15 (manufactured by Tokuyama Corporation, D50: 1.44 μm, specific surface area: 2 m 2 / g, D10 / D90: 0.53) · E-b: Sansil SS-10 (manufactured by Tokuyama Corporation, D50: 1.10 μm, specific surface area: 3 m 2 / g, D10 / D90: 0.44) · E-c: Sansil SS-07 (manufactured by Tokuyama Corporation, D50: 0.72 μm, specific surface area: 4 m 2 / g, D10 / D90: 0.65) · E-d: Sansil SS-04 (manufactured by Tokuyama Corporation, D50: 0.41 μm, specific surface area: 8 m 2 / g, D10 / D90: 0.67) · E-e: Sansil SS-03 (manufactured by Tokuyama Corporation, D50: 0.33 μm, specific surface area: 11 m 2 / g, D10 / D90: 0.63) · E-f: Sansil SS-01 (manufactured by Tokuyama Corporation, D50: 0.16 μm, specific surface area: 15 m 2 / g, D10 / D90: 0.57)

[0078] <Measurement of D10, D50, and D90> 100 mg of silica was mixed with 40 ml of water, and the mixture was irradiated with 40 W ultrasonic waves for 10 minutes to obtain a measurement sample in which silica was dispersed in water. The particle size distribution of the measurement sample was measured using a laser diffraction scattering type particle size distribution analyzer (manufactured by Beckman Coulter, Inc.: LS13 320). In the volume frequency distribution (particle size distribution) of the obtained particle diameters, the particle diameter at which the cumulative volume frequency from the smaller particle diameter side becomes 10% was defined as D10, the particle diameter at which the cumulative value becomes 50% was defined as D50, and the particle diameter at which the cumulative value becomes 90% was defined as D90.

[0079] <Measurement of specific surface area> A measurement sample was prepared by drying 2 g of silica in a nitrogen gas flow at 100° C. for 1 hour. The specific surface area of ​​the measurement sample was measured by the BET method (single-point nitrogen adsorption method) using a rapid surface area measuring device (SA-1000, manufactured by Shibata Scientific Co., Ltd.).

[0080] <Measurement of sphericity> 1000 silica particles contained in the silica were observed using a scanning electron microscope (SEM), and the sphericity of each particle was measured and the average value was calculated. The measurements were performed using an image processing program (AnalySIS manufactured by Soft Imaging System GmbH), and the sphericity was calculated as 4π × (area) / (perimeter) 2 As a result, it was found that all of the silica used had an average sphericity of more than 0.9, making them spherical silica.

[0081] <Determination of independence> The ratio (specific surface area) / (calculated specific surface area) was calculated to determine whether the silica was an independent particle. The calculated specific surface area is calculated by 6 / (density x D50). The density of silica is 2.2 g / cm 3 As a result, it was found that the above values ​​for all the silicas used were in the range of 0.85 to 1.35, and were independent.

[0082] <Measurement of liquidity> 0.2 mL of the adhesive of each Example and Comparative Example was aspirated and discharged using a dropper with a tip diameter of 2 mm. At this time, the case where the adhesive could be easily aspirated and discharged into the dropper was evaluated as ◯. The case where resistance was felt during aspirating or discharging, or air was mixed into the dropper was evaluated as ×.

[0083] <Measurement of linear expansion coefficient> The adhesive of each Example and Comparative Example was poured into a block-shaped mold, irradiated with ultraviolet light from the top and bottom for 5 minutes each, and heated at 100°C for 1.5 hours to produce a cured adhesive. This cured adhesive was polished and molded to 12mm x 6mm x 5.5mm to obtain a measurement sample. Using a thermomechanical analyzer (NETZSCH: TMA4000SE), each measurement sample was measured by the compression load method under the conditions of a sample length of 12mm, a load of 10g, a temperature range of 40 to 300°C, and a heating rate of 5°C / min. The linear expansion coefficient (CTE α1) was calculated based on the slope of the change in linear expansion coefficient from 50°C to 100°C.

[0084] <Measurement of storage modulus> The adhesive of each Example and Comparative Example was poured into a rectangular mold, irradiated with ultraviolet light from above and below for 5 minutes each, and heated at 100°C for 1.5 hours to produce a cured adhesive. This cured adhesive was polished to a size of 25mm x 5mm x 1mm to obtain a measurement sample. Using a dynamic viscoelasticity measuring device (NETZSCH: DMA 242 E Artemis), each measurement sample was measured in tensile measurement mode under the following conditions: sample length (chuck distance) 10mm, frequency 1Hz, temperature range 10 to 250°C, and heating rate 3°C / min. The storage modulus E' was obtained as a value at 25°C.

[0085] <Measurement of glass transition temperature> In the same manner as in the measurement of the storage modulus, measurement samples (25 mm x 5 mm x 1 mm hardened bodies) of each Example and Comparative Example were obtained. Using a dynamic viscoelasticity measuring device, each measurement sample was measured in the tensile measurement mode under the same conditions as above. The glass transition point was obtained as the peak temperature of the loss tangent given by the loss modulus / storage modulus.

[0086] Example 1 (A) 20 parts by mass of A-1, 50 parts by mass of A-2, and 20 parts by mass of A-3 as epoxy compounds, (B) 10 parts by mass of B-1 as oxetane compounds, (C) 3 parts by mass of C-1 as silane coupling agents, (D) 3 parts by mass of D-1 as photoacid generators, and (E) 128 parts by mass of Ea and 32 parts by mass of Ee as silica were mixed to obtain a photocationically curable adhesive, which is an adhesive composition of the embodiment. The physical properties of the silica used and the evaluation results of the physical properties of the cured body of the adhesive are shown in Table 1.

[0087] [Examples 2 to 6] Adhesives of the examples were obtained in the same manner as in Example 1, except that the type of (E) silica was changed as shown in Table 1. In Example 6, 96 parts by mass of Eb and 64 parts by mass of Ed were mixed as (E) silica.

[0088] [Comparative Examples 1 to 6] The adhesive of the comparative examples was obtained in the same manner as in Example 1, except that the type of (E) silica was changed as shown in Table 1. In Comparative Examples 1 and 2, 160 parts by mass of only (E-1) large particle silica was mixed as the (E) silica. In Comparative Example 3, 152 parts by mass of Eb and 8 parts by weight of Ed were mixed as the (E) silica. In Comparative Example 4, 72 parts by mass of Eb and 88 parts by weight of Ed were mixed as the (E) silica. In Table 1, Comparative Example 6 contains two types of (E-1) large particle silica, but for convenience of the table, Ec is entered in the column for (E-2) small particle silica.

[0089] [Table 1]

[0090] The evaluation results showed that all of the adhesives in Examples 1 to 6 had good fluidity, and the linear expansion coefficient of the cured product was less than 50 ppm / K, and the storage modulus was less than 8 GPa, so that the adhesives in each Example had good operability during use, and good linear expansion coefficient and storage modulus after curing.In addition, the glass transition point was 140°C or higher, so that the adhesives had excellent heat resistance. [Explanation of symbols]

[0091] 1 Camera module 2 Lenses 3. Telescope tube 4. Sealing Glass 5. Image sensor 6 Circuit Board 7. Cabinet 8 Hardened body

Claims

1. (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica; (E) Silica has (E-1) large particle size silica and (E-2) small particle size silica, (E-1) The average particle diameter D50 of the large-particle silica is 0.5 μm or more and 1.5 μm or less, (E-2) The average particle diameter D50 of the small particle silica is less than 0.5 μm, The difference between the average particle diameter D50 of the large-particle silica (E-1) and the average particle diameter D50 of the small-particle silica (E-2) is 0.5 μm or more; An adhesive composition, in which the content of the small particle size silica (E-2) in the silica (E) is 10 mass % or more and 50 mass % or less.

2. 2. The adhesive composition according to claim 1, wherein a content of the silica (E) relative to a total of 100 parts by mass of the epoxy compound (A) and the oxetane compound (B) is 100 parts by mass or more and 200 parts by mass or less.

3. An optical device comprising a cured product of the adhesive composition according to claim 1.

4. A method for producing an adhesive composition comprising (A) an epoxy compound, (B) an oxetane compound, (C) a silane coupling agent, (D) a photoacid generator, and (E) silica, the method comprising the steps of: A method for producing an adhesive composition, comprising mixing (E-1) large-particle-size silica having an average particle size D50 of 0.5 μm or more and 1.5 μm or less with (E-2) small-particle-size silica having an average particle size D50 of less than 0.5 μm and a difference of 0.5 μm or more from the average particle size D50 of the large-particle-size silica (E-1), such that the content of (E-2) small-particle-size silica in (E) silica is 10 mass % or more and 50 mass % or less.

Citation Information

Patent Citations

  • Laser module

    JP2005109413A

  • Photocurable adhesive composition and optical semiconductor device

    JP2016094509A

  • Adhesive for fixing optical components

    JP2018127507A

  • Dual-curing adhesive composition

    JP2021147584A

  • Adhesive composition and optical semiconductor device

    JP2022069039A